(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
The present work has the intention of approaching the analysis of the curricular designs linked to the New High School for the Ciudad Autónoma de Buenos Aires (CABA) district, its historiographical proposals, and their tensions, its general and specific objectives that are expressed in its content. The Curricular Designs to be analyzed, General Curricular Design and Oriented Curricular Design of the Baccalaureate in Social Sciences and Humanities, are being applied in all the educational establishments of the area of ​​the CABA this year. However, in this work the contents of Argentine History will be analyzed during the 19th and 20th centuries, covering the analysis of the superior years. This educational reform, both content and time allocated to them in some cases is presented as a challenge within the Institutes of Higher Education. At this point lays the second axis to address as the school actors in charge of putting into practice the NES and its curricular modifications in the field of the CABA are the teachers. Regarding teacher training and the relationship with NES contents, it will be taken as a sample as a training institution to the Higher Institute of Teaching Staff Dr. Joaquín V. González of the CABA. The work is intended to build from the two axes mentioned above 1) The Curricular Designs and 2) The Teacher Training.